ANALISIS PENERAPAN MANAJEMEN KELAS DALAM MENINGKATKAN KARAKTER KOMUNIKATIF PADA SISWA KELAS III SEKOLAH DASAR - Juliana; Siprianus Jewarut (ADIBA : JOURNAL OF EDUCATION, 2024)
This study aims to analyze the implementation of classroom management in enhancing communicative character among third-grade students at SDN 01 Bengkayang. Based on the research findings, it was found that a supportive classroom environment, the active role of teachers in facilitating interaction, and the application of various interactive teaching methods significantly contribute to the improvement of students' communicative skills.